Some results on cordiality labeling of generalized Jahangir graph - Roslan Hasni; S. Matarneh; Almothana Azaizeh (Indonesian Combinatorial Society (InaCombS), 2017)
In this paper we consider the cordiality of a generalized Jahangir graph J_n,m. We give sufficient condition for J_n,m to admit (or not admit) the prime cordial labeling, product cordial labeling and total product cordial labeling.